Indications for low-cost sustainability in Egyptian residential construction - Karim Kesseiba; Mennat-Allah El-Husseiny (Agathón)
Although sustainable building techniques and materials have always been used in the residential sector in Egypt, the calls for strategies to implement more environmentally friendly ways of the building have been rising. The study presents considerations on how and what can be done to make a sustainable and at the same time affordable design, not only with highly sophisticated systems; analyses the suburbs surrounding Cairo, describes case studies that have shown environmentally friendly solutions and concludes with a synoptic framework for affordable environmentally sustainable strategies which can be used for the housing sector.